Formation of hybrid phycobilisomes by association of phycobiliproteins from Nostoc and Fremyella - Canaani, Ora (1982)
Formation of phycobilisomes has been accomplished in vitro from isolated phycobiliprotein fractions obtained from the same blue-green alga (intrageneric) and from different blue-green algae (intergeneric). Phycobilisomes, which are supra-molecular complexes of phycobiliproteins, serve as major light-harvesting antennae for photosynthesis in blue-green and red algae. Intrageneric association into energetically functional phycobilisomes, previously reported to occur with Nostoc sp. allophycocyanin and phycoerythrin-phycocyanin complexes [Canaani, O., Lipschultz, C. A. & Gantt, E. (1980) FEBS Lett. 115, 225-229], has been obtained with Fremyella diplosiphon. By their spectral properties (absorption, fluorescence excitation, and emission) and electron microscopic images, the native and in vitro-associated phycobilisomes were virtually indistinguishable. Intergeneric phycobilisomes have been produced from allophycocyanin of Nostoc sp. strain Mac. and phycoerythrin-phycocyanin of F. diplosiphon, as well as from the reverse mixtures. The yield of intergeneric phycobilisomes, favored by higher phycobiliprotein content in 0.75 M phosphate, pH 7.0/2.0 M sucrose, was 40-60%. Energy transfer to the terminal long-wavelength-emitting allophycocyanin in the phycobilisomes was evident from the 670-675 nm fluorescence emission peaks. Furthermore, excitation spectra showed the contribution of the respective phycoerythrins (Fremyella, λ(max) 570; Nostoc, λ(max) 573 and 553 nm), as well as that of phycocyanin and short-wavelength-absorbing allophycocyanin. Phycobilisomes of Nostoc and Fremyella, analyzed by NaDodSO(4)/polyacrylamide gel electrophoresis, possessed a number of polypeptides having similar molecular weights: the usual α- and β-phycobilin-containing polypeptides of M(r) 15,000-22,000, a faint band at M(r)ca. 95,000, and a prominent band at M(r)ca. 31,000. The M(r) 31,000 polypeptide is assumed to provide the recognition site for attachment of the phycoerythrin-phycocyanin complexes with the allophycocyanin core. In vitro association was not obtained between allophycocyanin from Nostoc and phycoerythrin-phycocyanin complexes from Phormidium persicinum or Porphyridium sordidum.